Reporting Loss Carryovers in Financial Statements. - Williams, Doyle Z. (The Accounting Review, 1966)
Abstract The benefits derived from loss carry-backs should be reported in the financial statements in the year the loss occurred as an adjustment of the prior-year earnings. Such a procedure is based on sound theoretical grounds and has met widespread acceptance. Prevailing practice in accounting for the tax toss carryover seems to be questionable both on theoretical grounds as well as from a utilitarian viewpoint for financial reporting. Whenever an expected future economic benefit arises from the tax loss carryover, accountants have unjustifiably omitted it from the list of benefits or assets possessed by the firm. The balance sheet aspects of tax loss carryovers have too long been neglected. Moreover, in too many cases the earnings of subsequent profitable years have been relieved of any income tax burden resulting in misleading operating results. The procedures suggested in this paper for accounting for loss carryovers provide for recognizing the potential benefit gained from operating at a loss. To the extent that costs incurred giving rise to a loss are likely to be recovered, they should be carried forward on the balance sheet as assets to be associated with taxable income of later profitable years. This procedure achieves a proper matching of costs and revenues by requiring that the income tax reductions from the carry- over of operating losses be related to the years in which the losses occurred. Thus, the net loss of the loss year, as well as the net income of the other years to which the tax benefit is carried, is more fairly stated. In some, full accrual of a tax loss carryover results in effective financial reporting within the framework of existing accounting theory, especially when there are reasonably good indications that the carry- over will result in future income tax reductions.